Dementia with Lewy Bodies Clinical and Biological Aspects - Kosaka, Kenji; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
This book describes biological and clinical aspects of dementia with Lewy bodies (DLB), one of the most common types of progressive dementia, although in most cases the cause is unknown. The editor has made a major contribution to the understanding of the disease since he first reported DLB in 1976. Written by renowned experts in the field, the book discusses not only diagnostic criteria and clinical symptoms of DLB but also various imaging modalities and biological markers such as alpha-synuclein, which are useful for diagnosis of DLB. Dementia with Lewy Bodies is aimed at psychiatrists, neurologists, and researchers who are interested in DLB.
Part I. Introduction -- 1.History and latest concept of DLB -- 2.Epidemiology of DLB -- Part II. Biological Aspects -- 3.Neuropathology of DLB -- 4.Biochemistry of DLB -- 5.Molecular biology of DLB -- Part III. Clinical Aspects -- 6.Clinical diagnostic criteria of DLB -- 7.Cognitive impairments of DLB -- 8.BPSD in DLB -- 9.Parkinson symptoms of DLB -- 10.Autonomic symptoms of DLB -- Part IV. Biological Markers -- 11.CT, MRI, SPECT and PET in DLB -- 12.DaT Scan in DLB -- 13.MIBG myocardial scintigraphy in DLB -- 14.Alpha-synuclein in cerebrospinal fluid -- 15.Electroencephalography in DLB -- 16.Ventilatory response to hypercapnia -- Part V. Treatment -- 17.Pharmacotherapy in DLB -- 18.Kampo medicine in DLB.
Keywords: Medicine; Neuroradiology; Neurology; Psychiatry; Medicine & Public Health; Psychiatry; Neurology; Neuroradiology